Evolution characteristics of impact weather system and SST signals during years of anomalous Meiyu onset over the Yangtze-Huaihe River Basin - Jin, Xiaoxia; Ma, Yutong; Liu, Mei; Zhong, Shanshan (Frontiers in Earth Science, 2023)
This article investigates the climatic characteristics of Meiyu over the Yangtze-Huaihe River Basin and the primary impact system based on Meiyu onset data from 1954 to 2020, precipitation during the Meiyu Period, NCEP/NCAR reanalysis data, sea surface temperature (SST) data of NOAA, and western Pacific subtropical high (sub-high) data provided by the National Climate Center. The main analytical method used is synthetic analysis. The results indicate that the Meiyu onset date has enormous interannual variation. The date of the earliest Meiyu emergence is 27 days prior to the latest. There is a strong relationship between the duration of Meiyu and rainfall. The start of Meiyu correlates with the northward motion of the South Asia High, the northward jump of the westerly jet, the northward jump of the subtropical high, and the northward motion of the low-level jet. In the early Meiyu years featured in this study, the northward jump of the aforementioned systems occurred earlier and the position of the westerly jet shifted from 34–35°N to 38–40°N, which is much further north than its position under typical climatic circumstances. From late May to early June, the subtropical high was extraordinarily powerful, the ridgeline reached 20°N, and its position was further to the north. In years with a late Meiyu onset, the position of the westerly jet and the ridgeline were further south than the climatological average from early to late June; the jump to the north was not evident until late June. In addition, SST anomalies of the Indian Ocean and Pacific Ocean are significant external forcing variables that influence the Meiyu start date. The high SST of the equatorial Indian Ocean and the equatorial tropical eastern Pacific in the autumn of the preceding year and the high SST of the equatorial Indian Ocean in the spring of that year are prophase indicators of an early Meiyu start in the Yangtze-Huaihe River Basin.